(untitled) (International Journal of Applied Research in Management and Economics, 2023)
This paper explains the process by which a global corporate giant was made to account for its social responsibility by studying the conflict between Coca-Cola company and the local community in Plachimada (a small village in the south Indian state of Kerala) as a case study. The paper argues that the company suffered a long judicial battle and loss of reputation and finally lost ‘its license to operate’ for not discharging its responsibility to the local community (a major stakeholder). The analysis of the events in this conflict seems to suggest that the combination of new social movements and consumer activism in defence of human rights and environmental protection holds the promise of making the large global corporations more accountable for their social responsibilities. Fuelled by the speed of the internet and the resultant reach of media (including social media), these movements have become more effective and stronger during the last twenty years and the corporates therefore can ignore the responsibilities that society expects them to embrace only at their own peril.